Application of Cadexomer Iodine Powder to Minimize Biofilms in Diabetic Foot Ulcer Patients (DFU) at Griya Afiat Wound Care Clinic: Case Report - S, Moh Gifari; Jannah, Uyunul; Tahir, Takdir; Yusuf, Saldy (Jurnal Keperawatan Respati Yogyakarta, 2020)
Every wound in diabetics has the potential to experience a setback in healing into a chronic wound so that the wound also has the potential to form into biofilm. One of the modern dressings commonly used to suppress the growth of biofilm is Cadexomer Iodine Powder. However, there is still limited research that addresses directly related to the effectivity of Cadexomer Iodine Powder towards wound healing. Therefore, this report aims to evaluate effectiveness Cadexomer Iodine Powder on wound healing with biofilm problems at Griya Afiat Makassar's wound care clinic. The study aimed to identify the effectiveness of Cadexomer Iodine Powder in minimizing biofilms in diabetic foot ulcer (DFU) patients. This study was conducted on one patient who was followed prospectively for 32 days from 10 July to 10 August 2019 with 10 treatments. The dressing used for wound care is Cadexomer Iodine Powder. To evaluate the reduction in the number of biofilms performed by the expert wound when treatment continues. Meanwhile, to evaluate the wound healing process, the modified Bates-Jensen Wound Assessment was used. This report shows a decrease in biofilm from the first treatment to the last treatment with the number of biofilms in the first treatment (+++) to a few (+) in the 10th treatment. The treatment also took a short period of time which is 32 days with a wound condition at the beginning of treatment which is 30% of slough and 70% of granulation experiencing a very swift healing in the 10th treatment to 40% of epithelium and 60% of granulation. Cadexomer Iodine Powder is very effective in the process of wound treatment which can be seen through the reduction of biofilms. In addition, wound healing is much better with shorter treatment time as a proof.